Does bribery help or hurt firm growth around the world? - Zhou, J.; Peng, Mike (Springer New York LLC, 2012)
Does bribery help or hurt firm growth? Some suggest that bribery greases the wheel of commerce, while others believe that bribery sands the wheel of growth. We argue that firms endogenously choose their level of bribery according to their environments and that the benefits and costs may differ for different types of bribery. Specifically, small firms are more likely to be forced to engage in bribery, while big firms may strategically engage in bribery. Utilizing a large, cross-country survey sample involving 2,686 firms in 48 countries, we find that firms choose a higher level of bribery when embedded in under-developed market-supporting institutions. After controlling for endogenous bribery choices, bribery hurts firm growth for small and medium-sized firms, but not for large firms.